Crystal structure of [tBuMgCl]2[MgCl2(Et2O)2]2 - Maurice Metzler; Michael Bolte; Matthias Wagner; Hans-Wolfram Lerner (Acta Crystallographica Section E: Crystallographic Communications, 2023)
The title compound, di-μ3-chlorido-tetra-μ2-chlorido-tetrakis(diethyl ether-κO)bis(1,1-dimethylethyl)tetramagnesium, [Mg4(C4H9)2Cl6(C4H10O)4], features an Mg4Cl6 open-cube cluster. The two four-coordinate Mg2+ ions show an almost tetrahedral coordination, whereas the two six-coordinate Mg2+ ions have their ligands in an octahedral environment. The Mg—Cl bond lengths differ depending on the coordination number (2 or 3) of the bridging μ-Cl− ligands. There are few comparable structures deposited in the Cambridge Structural Database.